The Dead May Kill You: Do Ancestor Spirit Beliefs Promote Cooperation in Traditional Small-Scale Societies? - White, Claire (Journal of cognition and culture, 2022)
There is considerable evidence that beliefs in supernatural punishment decrease self-interested behavior and increase cooperation amongst group members. To date, research has largely focused on beliefs concerning omniscient moralistic gods in large-scale societies. While there is an abundance of ethnographic accounts documenting fear of supernatural punishment, there is a dearth of systematic cross-cultural comparative quantitative evidence as to whether belief in supernatural agents with limited powers in small-scale societies also exert these effects. Here, we examine information extracted from the Human Relations Area Files on cultural discourse about the recently deceased, local ancestor spirits, and mortuary practices across 57 representative cultures. We find evidence that in traditional small-scale societies ancestor spirits are commonly believed to be capable of inflicting harm, with many attendant practices aimed at mitigating this danger. However, such beliefs do not appear to promote cooperation, as ancestor spirits seem to be concerned with interactions between themselves and the living, and to prioritize their own welfare. Many attendant practices are inconsistent even with bipartite cooperation with ancestors that could be viewed as a model for other relationships. The broader implications of this research for the cultural evolution of religion are discussed.